2022
DOI: 10.1177/00034894211072996
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Educational Podcast Use Among Otolaryngology Residents

Abstract: Objective: Medical podcasts are becoming increasingly available; however, it is unclear how these new resources are being used by trainees or whether they influence clinical practice. This study explores the preferences and experiences of otolaryngology residents with otolaryngology-specific podcasts, and the impact of these podcasts on resident education and clinical practice. Methods: An 18-question survey was distributed anonymously to a representative junior (up to post-graduate year 3) and senior (post-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Reviewing the available data shows that podcasts play a role in undergraduate and graduate medical education [10][11][12]. Also, when used by learners from other specialties, podcasts shape their medical knowledge and alter their clinical practice [13]. It has also been shown that medical professionals prefer podcasts to other forms of media in education delivery, specifically, podcasts over video recordings, printed media, and in-person education [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the available data shows that podcasts play a role in undergraduate and graduate medical education [10][11][12]. Also, when used by learners from other specialties, podcasts shape their medical knowledge and alter their clinical practice [13]. It has also been shown that medical professionals prefer podcasts to other forms of media in education delivery, specifically, podcasts over video recordings, printed media, and in-person education [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…There has been a growing availability of online educational resources within the field of otolaryngology, such as recorded lectures, surgical videos, and podcasts 1–4 . However, these resources often lack the structure and breadth necessary to comprise a complete residency didactic curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing availability of online educational resources within the field of otolaryngology, such as recorded lectures, surgical videos, and podcasts. [1][2][3][4] However, these resources often lack the structure and breadth necessary to comprise a complete residency didactic curriculum. For didactic learning to be maximally effective, it should engage residents as adult learners and incorporate established principles of adult learning theory that emphasize learners as intrinsically motivated, self-directed, and problem-oriented, with prior experiences that shape their learning.…”
Section: Introductionmentioning
confidence: 99%
“… 12 17 Likewise, podcasts have facilitated increased understanding of educational content at the resident training level, such as electroencephalography among anesthesiology residents and clinical decision-making among otolaryngology residents. 18 19 20 Podcasts also serve the attending physician population, offering continuing medical education (CME) credit. 15 A survey of retina society members found that 41% of respondents reported listening to at least one podcast weekly, with 68.3% using podcasts during their commute to stay up-to-date on the latest research.…”
mentioning
confidence: 99%